Pyogenic liver abscess and sepsis caused by mixed anaerobic bacteria in an immunocompetent adult: a case report - Fan, Ziwen; Mei, Mu; Chen, Cen (Frontiers in Medicine, 2025)
BackgroundAnaerobic bacterial communities in the digestive tract play an important role in digestive tract infections and aspiration pneumonia. However, ectopic infections originating from these communities are uncommon.Case reportWe present a rare case of a 64-year-old immunocompetent female was admitted with no significant medical history who developed a pyogenic liver abscess and sepsis caused by multiple anaerobic bacteria of digestive tract origin. Metagenomic next-generation sequencing (mNGS) detected four types of anaerobic bacteria in both peripheral blood and abscess puncture fluid. Culture confirmed the presence of three of these microorganisms. Treatment with a combination of meropenem and metronidazole resulted in the patient’s subsequent recovery and discharge.ConclusionThis report highlights the occurrence of ectopic infections caused by multiple anaerobic bacteria leading to pyogenic liver abscess and sepsis, underscoring the importance of considering anaerobic bacteria and conducting rapid comprehensive pathogen detection in clinical practice.